2008
DOI: 10.1007/s12275-007-0181-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies in response to Legionella species, analysis of a healthy population from Jeollanam-do Province, Korea

Abstract: Seroepidemological investigation of antibodies to Legionella species in 500 healthy individuals from a single geographical location in Korea was conducted by indirect fluorescent antibody assay (IFA). Considering an antibody titer of > or =1:128 as positive reaction, 15.2% of total sera were positive. In males and females older than 40 years old, levels of IgM and IgG were 1.2% and 14%, respectively. The sera with antibody titers of > or =1:128 to Legionella species accounted for 85 sera, and 9 sera of these w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
3
0
2
Order By: Relevance
“…No or only very weak responses were detectable against the non-persistent human pathogen L pneumophila (figure 2B). This is consistent with previous reports which state <20% of a population to have antibodies against L pneumophila 36 37…”
Section: Resultssupporting
confidence: 94%
“…No or only very weak responses were detectable against the non-persistent human pathogen L pneumophila (figure 2B). This is consistent with previous reports which state <20% of a population to have antibodies against L pneumophila 36 37…”
Section: Resultssupporting
confidence: 94%
“…Healthy populations across geographically diverse parts of the United States, Europe, the Middle East, Australia, Japan, South Korea, China, and former Soviet states display a large variation in seroprevalence for all legionellae, which additionally supports a reexamination of local Legionella exposures and the value of Lp1-specific UATs for diagnosing most LD cases (153)(154)(155)(156)(157)(158)(159)(289)(290)(291)(292)(293)(294)(295)(296)(297)(298)(299)(300)(301)(302)(303). This underscores a pressing need for the development of more inclusive Legionella rapid diagnostics; to be useful in a basic laboratory or POC setting, a pan-Legionella UAT would ostensibly be as simple to perform as current tests while detecting additional species and serogroups with similar efficiencies.…”
Section: Urinary Antigen Testmentioning
confidence: 96%
“…Indeed, seroprevalence studies in many countries have demonstrated potential ongoing exposure to diverse Legionella serogroups and species, which typically contrasts with the greater clinical prevalence of Lp1 (153)(154)(155)(156)(157)(158)(159)(160). As such, substantial effort has been devoted to characterizing Lp1 virulence determinants, such as secreted effectors or surface factors.…”
Section: Epidemiology and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Οη θάξηεο απηέο νη νπνίεο αλαπηχρζεθαλ ζηα κέζα ηεο δεθαεηίαο απφ ηε Life Technologies, κπνξνχλ πνιχ γξήγνξα λα αληρλεχζνπλ έθθξαζε γνληδίσλ ζε δηάθνξα ζηάδηα κηαο λφζνπ. Δξεπλεηέο ζην CDC αλάπηπμαλ TACs γηα ηελ ηαπηφρξνλε αλίρλεπζε > 20 αλαπλεπζηηθψλ παζνγφλσλ, ζπκπεξηιακβαλνκέλνπ ηεο Λεγεσλέιιαο (Diaz et al, 2013;Kodani and Winchell, 2012 (Yanez et al, 2005;Sethi, Gore and Sethi, 2007;Fuchslin et al, 2010;Allegra et al, 2011;Reidt et al, 2011;Keserue et al, 2012;Albalat et al, 2012;Bedrina et al, 2013 (Granados et al, 1989;Lee et al, 2008). Γηάθνξεο κειέηεο έρνπλ δείμεη φηη ε ρξήζε ησλ κνλνθισληθψλ αληηζσκάησλ κπνξεί λα είλαη αλεπαξθήο γηα ηε ζαθή δηάθξηζε ησλ ζηειερψλ πνπ έρνπλ πξνθαιέζεη λφζν θαη ησλ αληίζηνηρσλ πεξηβαιινληηθψλ ζηειερψλ ηεο L.…”
Section: Microfluid Taqman Low-density Microarray Cards (Tac)unclassified